2011
DOI: 10.1002/mrc.2749
|View full text |Cite
|
Sign up to set email alerts
|

Saturation‐dependent nuclear magnetic resonance relaxation of fluids confined inside porous media with micrometer‐sized pores

Abstract: In the present study, we investigate the relationship between the relaxation rate and the filling factor in partially saturated porous media. The filling fluids are polar (water, acetone) and nonpolar (cyclohexane, hexane). The porous sample is a silica glass (Vitrapor#5) with the nominal mean pore size of d = 1 µm ( ± 0.6 µm). All nuclear magnetic resonance relaxation experiments are performed at 20 °C using a NMR instrument operable at 20 MHz proton resonance frequency. The experimental results are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…A long lifetime T 2 distribution component with a peak at 42 ms was observed. This long lifetime T 2 peak is associated with higher water saturation in larger size pores . According to Eqn , the water volume, V , increased, but the contacting area between water and pore surface, S , did not change.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A long lifetime T 2 distribution component with a peak at 42 ms was observed. This long lifetime T 2 peak is associated with higher water saturation in larger size pores . According to Eqn , the water volume, V , increased, but the contacting area between water and pore surface, S , did not change.…”
Section: Resultsmentioning
confidence: 90%
“…This long lifetime T 2 peak is associated with higher water saturation in larger size pores. [14,27] According to Eqn (6), the water volume, V, increased, but the contacting area between water and pore surface, S, did not change. Water is the wetting phase in this flooding process.…”
Section: Resultsmentioning
confidence: 97%
“…, and further application is important for cross‐checking. Recent uses of these methods, like for example NMR to discern different liquid distributions on the surface of pores, should clarify the features of the CCs. The generalization of the results found in CCs to other environments, especially in confined ones, is also a task for upcoming research.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the presence of the porous medium disrupted the hydrogen bonding network for polyols. Simina et al 331 investigated the relaxation rates of polar and non-polar fluids confined in micrometer-sized pores of a silica glass. Rajeswari and co-workers 332 described 1 H T 1 dispersion measurements for a liquid-crystal forming liquid, both in the isotropic and nematic phase, confined to a random porous network.…”
Section: Synthetic Polymers In Solutionmentioning
confidence: 99%